Proceedings of the 33rd International ACM SIGIR Conference on Research and Development in Information Retrieval 2010
DOI: 10.1145/1835449.1835667
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between effectiveness and accessibility

Abstract: Typically the evaluation of Information Retrieval (IR) systems is focused upon two main system attributes: efficiency and effectiveness. However, it has been argued that it is also important to consider accessibility, i.e. the extent to which the IR system makes information easily accessible. But, it is unclear how accessibility relates to typical IR evaluation, and specifically whether there is a trade-off between accessibility and effectiveness. In this poster, we empirically explore the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…For example, Azzopardi et al [2] showed that a positive relation exists between effectiveness and retrievability. Measuring effectiveness using precision at 10 (P@10) & Mean Average Precision (MAP), the results showed that as the effectiveness increases, the retrievability bias tends to decrease.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Azzopardi et al [2] showed that a positive relation exists between effectiveness and retrievability. Measuring effectiveness using precision at 10 (P@10) & Mean Average Precision (MAP), the results showed that as the effectiveness increases, the retrievability bias tends to decrease.…”
Section: Related Workmentioning
confidence: 99%
“…Experiment 4: Altering the Number of Documents for Expansion The final experiment follows the same method as Experiment 3 however, the number of documents that terms are extracted from are altered. 10 terms are extracted from a varying number from the top x documents (1,2,3,4,5,6,7,8,9,10,12,15,20,25,50). …”
Section: Experiments 3: Altering the Number Of Terms For Expansionmentioning
confidence: 99%
“…where q is a query from the large query set Q. k dq is the rank at which d is retrieved given q, therefore the utility function f (k dq , c) determines the score that document d attains for query q given the rank cutoff c. r(d) is calculated by summing over all queries q in query set Q. Theoretically, Q represents the universe of all possible queries, but in practice Q is very large set of queries [1,2,4,5,10]. The standard measure of retrievability used employs the utility function f (k dq , c), such that if a document, d, is retrieved in the top c documents given q, then f (k dq , c) = 1, otherwise f (k dq , c) = 0.…”
Section: Introductionmentioning
confidence: 99%
“…Here we will describe and discuss the various efforts that have tried to understand the relationship between retrievability and effectiveness [19,18,40,4,39]. Firstly, from a theoretical point of view, we will discuss the different possible relationships and how retrievability can impact upon both effectiveness and efficiency.…”
Section: Relationships With Retrievability (1hr)mentioning
confidence: 99%
“…The conceptual / hypothesised relationship between retrievability and performance [4] 2. Retrievability and Efficiency 3.…”
Section: Relationships With Retrievability (1hr)mentioning
confidence: 99%